Pott's disease: a major issue for an unaccompanied refugee minor. Issue 3 (21st November 2016) - Papan, Cihan; von Both, Ulrich; Kappler, Matthias; Kammer, Birgit; Griese, Matthias; Huebner, Johannes
Abstract : The incidence of TB in children in Germany has been on a rise since 2008, especially among foreign-born individuals. With rapidly increasing numbers of refugees from the numerous areas of conflict, this increase in incidence is not expected to halt, neither in Germany nor in Europe in general. We report a case of insufficient tracking in a 16-year-old unaccompanied refugee minor from Somalia who had a positive interferon γ release assay on arrival in Germany. No actions were undertaken, until 6 months later, an X-ray showed prominent hilar enlargement. Nine  months later, the patient presented to our hospital with abdominal pain, vomiting and B symptoms. Workup revealed a paravertebral abscess due to Pott's disease, a skeletal manifestation of Mycobacterium tuberculosis disease. The patient made a full recovery after a combination therapy for a total of 9 months.